Internet Addiction and Related Clinical Problems: A Study on Italian Young Adults - Zamboni, Lorenzo; Portoghese, Igor; Congiu, Alessio; Carli, Silvia; Munari, Ruggero; Federico, Angela; Centoni, Francesco; Rizzini, Adelelmo Lodi; Lugoboni, Fabio (Frontiers in Psychology, 2020)
The considerable prominence of internet addiction (IA) in adolescence is at least partly explained by the limited knowledge thus far available on this complex phenomenon. In discussing IA, it is necessary to be aware that this is a construct for which there is still no clear definition in the literature. Nonetheless, its important clinical implications, as emerging in recent years, justify the lively interest of researchers in this new form of behavioral addiction. Over the years, studies have associated IA with numerous clinical problems. However, fewer studies have investigated what factors might mediate the relationship between IA and the different problems associated with it. Ours is one such study. The Italian version of the SCL-90 and the IAT were administered to a sample of almost 800 adolescents aged between 16 and 22 years. We found the presence of a significant association between IA and two variables: somatization (β= 7.80; p < .001) and obsessive-compulsive symptoms (β= 2.18; p < .05). In line with our hypothesis, the results showed that somatization predicted the relationship between obsessive-compulsive symptoms and IA (β= -2.75; t= -3.55; p< 0.001), explaining 24.5% of its variance (ΔR2=1.2%; F =12.78; p<0.01). In addition, simple slopes analyses revealed that, on reaching clinical significance (+1 SD), somatization showed higher moderation effects in the relationship between obsessive-compulsive symptoms and IA (β = 6.13; t = 7.83; p < .001). These results appear to be of great interest due to the absence of similar evidence in the literature, and may open the way for further research in the IA field. Although the absence of studies in the literature does not allow us to offer an exhaustive explanation of these results, our study supports current addiction theories which emphasize the important function performed by the enteroceptive system, alongside the more cited reflexive and impulsive systems.